Arts of engagement: taking aesthetic action in and beyond the Truth and Reconciliation Commission of Canada - Martin, Keith; Robinson, Dylan (Wilfrid Laurier University Press, 2016)
It's about the role that music, film, visual art, and Indigenous cultural practices play in and beyond Canada's Truth and Reconciliation Commission on Indian Residential Schools. The essays question the ways in which components of the reconciliation, such as apology and witnessing, have social and political effects for residential-schools survivors, intergenerational survivors, and settler publics."– Provided by publisher
Section: viii, 374 pages : illustrations ; 23 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé